The Energy Density of the Universe in the Vector Model for Gravitational Field - On, Vo Van (Communications in Physics, 2019)
We show that, in the framework of the vector model of gravitational field, the total mass density and the mass of the Universe are quite the same as of experimental observed ones \(ρ_{\text{total}} \simeq 1.0 × 10^{−29}\) g/cm\(^3\) and \(M_{\text{universe}}\simeq 1053\) kg.